Features of Extended Reality Environments in Semiconductor Fabrication Process Education: A Scoping Review - Dennis R. Parnell; Atayliya N. Irving; Connor S. Smith; Amy G. Buhler; Jeremy A. Magruder Waisome (IEEE Access)
The passing of the CHIPS and Science Act in the United States has signaled a renewed interest in expanding the domestic semiconductor industry. To fuel this expansion and the new job opportunities it creates, academic institutions and companies alike will need to educate and train a new and growing workforce in the field of semiconductor fabrication. Unfortunately, the ability to provide hands-on learning experiences currently lacks accessibility due to the costs of starting and maintaining a cleanroom. However, extended reality (XR) offers a lower-cost alternative to address this issue. This scoping review seeks to determine the features present in existing XR environments used for semiconductor fabrication process education. Using the framework outlined by Arksey and O’Malley, only five conference articles from an initial pool of 1,116 articles were included in the review. These papers were all published between 2018 and 2023 and only focused on virtual reality devices. Across the five articles, 12 different features were identified. Notable limitations of this work include restricting the scope to six semiconductor fabrication processes, as well as excluding articles that did not specify the XR device used. Overall, the findings show that there has been very little research on the use of XR in the field of semiconductor fabrication education.